Measuring the solubility of benzoic acid in room temperature ionic liquids using chronoamperometric techniques - He, W.; Silvester, Debbie; Streeter, I.; Aldous, L.; Hardacre, C.; Compton, R. (John Wiley and Sons Ltd, 2009)
The electrochemical reduction of benzoic acid (BZA) has been studied at platinum micro-electrodes (10 and 2 µm diameters) in acetonitrile (MeCN) and six room temperature ionic liquids (RTILs): [C2mim][NTf2], [C4mim][NTf2], [C4mpyrr][NTf2], [C4mim][BF4], [C4mim][NO3] and [C4mim][PF6] (where [Cnmim]+ = 1-alkyl-3-methylimidazolium, [NTf2]− = bis(trifluoromethylsulphonyl)imide, [C4mpyrr]+ = N-butyl-N-methylpyrrolidinium, [BF4]− = tetrafluoroborate, [NO3]− = nitrate and [PF6]− = hexafluorophosphate). Based on the theoretical fitting to experimental chronoamperometric transients in [C4mpyrr][NTf2] and MeCN at several concentrations and on different size electrodes, it is suggested that a fast chemical step preceeds the electron transfer step in a CE mechanism (given below) in both RTILs and MeCN, leading to the appearance of a simple one-electron transfer mechanism.The six RTIL solvents and MeCN were saturated with BZA, and potential-step chronoamperometry revealed diffusion coefficients of 170, 4.6, 3.2, 2.7, 1.8, 0.26 and 0.96 × 10−11 m2 s−1 and solubilities of 850, 75, 78, 74, 220, 2850 and 48 mM in MeCN and the six ionic liquids, respectively, at 298 K. The high solubility of BZA in [C4mim][NO3] may suggest a strong interaction of the dissolved proton with the nitrate anion. Although there are relatively few literature reports of solubilities of organic solutes in RTILs at present, these results suggest the need for further studies on the solubilities of organic species (particularly acids) in RTILs, because of the contrasting interaction of dissolved species with the RTIL ions. Chronoamperometry is suggested as a convenient methodology for this purpose.